Universal Basic AI Access: Countering the Digital Divide - Petr Špecián; Jitka Špeciánová (Acta Informatica Pragensia)
Generative artificial intelligence (GAI) presents an opportunity to democratize access to high-performance, easy-to-use tools of productivity enhancement. However, current adoption patterns suggest that it may instead amplify existing digital divides. The aim of this paper is to propose a policy intervention to ensure equitable access to frontier GAI capabilities: the universal basic AI access (UBAI). Relying on literature research and theoretical analysis, we examine two implementation variants: a voucher-based system making use of commercial providers (UBAI-Light) and direct public provision of GAI services (UBAI-Heavy). We also consider a gradual implementation approach that allows policymakers to support an immediate capture of democratizing benefits while building the capacity for a more substantive future government involvement, should it become necessary. Given the rapid pace of GAI development and adoption, we conclude that timely implementation of UBAI could help prevent the spread of GAI-driven inequalities before they become entrenched.